Le tappe italiane del Trimble Express 2010 - Leonardi, Sandra (GEOmedia, 2010)
Trimble Express stopped over Italy Trimble Express stopped in Italy, in 6 cities. The european road show has been set up to promote the latest news regarding Trimble technologies such as Trimble Access, the software that offers to survey teams a new approach in surveying; Trimble Access expedites data collection, processing, analysis, and delivery through improved workflows, collaboration and control.